Application of Carbon Nanofiber-Modified Concrete in Industrial Building Design. (25th January 2023) - Liu, Tianjie
Abstract : In order to explore the influence law and action mechanism of carbon nanofibers on the basic mechanical properties of concrete, the author proposes the mechanical properties and microscopic mechanism of carbon nanofiber-modified concrete. Concrete was prepared with different dosages of carbon nanofibers, and the compressive strength, flexural strength, and splitting strength of carbon nanofiber-modified concrete were tested, and the modification mechanism was explored. Experimental results show that an appropriate amount of carbon nanofibers can improve the mechanical properties of concrete. When the dosage is 0.3%, the mechanical properties of carbon nanofiber-modified concrete are the best, and its compressive strength, flexural strength, and split tensile strength are increased by 9.2%, 13.2%, and 17.5%, respectively, compared with plain concrete. Carbon nanofibers can form a three-dimensional network structure inside the concrete, which can improve the microscopic morphology of the concrete, enhance the toughness and integrity of the concrete, fill the pore defects inside the concrete, refine the pore size distribution, and consume part of the fracture failure energy when the concrete is damaged.